2004
DOI: 10.1080/09637480310001642484
|View full text |Cite
|
Sign up to set email alerts
|

Survival ofLactobacillus acidophilusLA-5 andBifidobacterium bifidumBB-02 in white-brined cheese

Abstract: The viability of probiotic cultures used as adjunct cultures including Bifidobacterium bifidum BB-02 and Lactobacillus acidophilus LA-5 in white-brined cheese was investigated. The microbiological and biochemical properties of cheeses were assessed throughout 90 days of storage. Two inoculum rates for probiotic starters (2.5% and 5.0%, v/v, corresponding to (1.0-1.3)x10(9) cfu/g and (2.0-2.1)x10(9) cfu/g, respectively) were compared with the control cheese. Results obtained showed that a higher inoculum rate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 23 publications
1
29
0
1
Order By: Relevance
“…Similarly, Ryhänen et al (2001) found counts of L. acidophilus over 6.0 log cfu g -1 in Festivo cheese during 16 weeks of storage. Yilmaztekin et al (2004) reported counts of L. acidophilus La-5 in whitebrined cheese approximately 6.0 log cfu g -1 after 90 days of storage. Vinderola et al (2000) tested the addition of L. acidophilus in mixed culture with different bifidobacteria (Bifidobacterium sp., B. bifidum, and B. longum) to Argentinian fresco cheese and observed counts of L. acidophilus above 6.0 log cfu g -1 after 60 days of storage.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Ryhänen et al (2001) found counts of L. acidophilus over 6.0 log cfu g -1 in Festivo cheese during 16 weeks of storage. Yilmaztekin et al (2004) reported counts of L. acidophilus La-5 in whitebrined cheese approximately 6.0 log cfu g -1 after 90 days of storage. Vinderola et al (2000) tested the addition of L. acidophilus in mixed culture with different bifidobacteria (Bifidobacterium sp., B. bifidum, and B. longum) to Argentinian fresco cheese and observed counts of L. acidophilus above 6.0 log cfu g -1 after 60 days of storage.…”
Section: Resultsmentioning
confidence: 99%
“…lactis in the manufacture of Beyaz peynir produced a good quality cheese unless the level of inoculum was high [5]. Recently, Yilmaztekin et al [85] investigated the potential of incorporating Bifidobacterium BB-12 and Lb. acidophilus LA-5 as adjunct cultures in Beyaz peynir production.…”
Section: Microbiological and Biochemical Aspectsmentioning
confidence: 99%
“…However, increasing the level of salt (> 20% NaCl brine) causes some textural [47] and hydrolytic and oxidative rancidity problems [48] in Gaziantep cheese. Reduction of the fat-in-dry matter content (FDM, 50.4, 33.4 or 13.5%) and scalding the curd at different temperatures (75,85 or 95 • C) affected the rheological and functional properties of Gaziantep cheese [39,40]. Reducing the fat-in-dry matter and increasing the scalding temperature improved the textural characteristics of the cheese, including hardness, gumminess, cohesiveness and springiness values, while these treatments reduced the meltability of Gaziantep cheese.…”
Section: Gaziantep Cheesementioning
confidence: 99%
“…Currently, probiotic cultures are successfully incorporated into large number of fermented milk products, especially in yogurts, ice creams [18,[20][21][22][23][24][25][26] and cheddar cheese [18,[27][28][29][30][31], but scarcely in white brined cheese [32][33][34][35][36]. In recent years, the consumption of cheese has increased rapidly.…”
Section: Introductionmentioning
confidence: 99%